Pola Integrasi Kultur Pesantren pada Pengembangan Kurikulum Sekolah (Studi Exploratif Sekolah Menengah Atas Islam Plus Bina Insani Sususkan Kabupaten Semarang) - Rifqi Lutfi; Imam Sutomo (Attractive : Innovative Education Journal, 2024)
The current development of Islamic boarding school education is very promising, even though one Islamic boarding school has different models to another, almost the majority of Islamic boarding schools have adopted and implemented a formal education curriculum in the form of schools (madrasas) or even universities. Schools and Islamic boarding schools are two educational institutions, each of which has advantages and characteristics that are different from each other. The curriculum is an important part in achieving educational goals . The integration of Islamic boarding school culture into the formal curriculum is an effort to maintain good old traditions and adopt something new and considered better. Writer use approach qualitative through method interview, observation, And documentation. Whereas technique analysis data using qualitative data analysis with collecting, reducing procedures data, presenting data, and drawing conclusions which are then verified. Research findings: (1) Curriculum development at SMA Islam Plus Bina Insani Susukan indirectly follows the topdown /administrative development model.(2) The integration of Islamic boarding school culture into curriculum development at Bina Insani Susukan High School is carried out by; Integration of Islamic boarding school essential values in the Learning Implementation Plan and school vision and mission, Addition of Arabic Language Subjects, Selection of religious extracurriculars, Living Sunah. Appreciation of individual differences